The effect of foot massage on long-term care staff working with older people with dementia: a pilot, parallel group, randomized controlled trial - Moyle, W.; Cooke, M.; O'Dwyer, S.; Murfield, J.; Johnston, A.; Sung, Billy (BioMed Central, 2013)
Background: Caring for a person with dementia can be physically and emotionally demanding, with many long-term care facility staff experiencing increased levels of stress and burnout. Massage has been shown to be one way in which nurses’ stress can be reduced. However, no research has been conducted to explore its effectiveness for care staff working with older people with dementia in long-term care facilities. Methods: This was a pilot, parallel group, randomized controlled trial aimed at exploring feasibility for a larger randomized controlled trial. Nineteen staff, providing direct care to residents with dementia and regularly working ≥ two day-shifts a week, from one long-term care facility in Queensland (Australia), were randomized into either a foot massage intervention (n=9) or a silent resting control (n=10). Each respective session lasted for 10-min, and participants could receive up to three sessions a week, during their allocated shift, over four-weeks. At pre- and post-intervention, participants were assessed on self-report outcome measures that rated mood state and experiences of working with people with dementia. Immediately before and after each intervention/control session, participants had their blood pressure and anxiety measured. An Intention To Treat framework was applied to the analyses. Individual qualitative interviews were also undertaken to explore participants’ perceptions of the intervention.Results: The results indicate the feasibility of undertaking such a study in terms of: recruitment; the intervention; timing of intervention; and completion rates. A change in the intervention indicated the importance of a quiet, restful environment when undertaking a relaxation intervention. For the psychological measures, although there were trends indicating improvement in mood there was no significant difference between groups when comparing their pre- and post- scores. There were significant differences between groups for diastolic blood pressure (p= 0.04, partial η2=0.22) and anxiety (p= 0.02, partial η2=0.31), with the foot massage group experiencing greatest decreases immediately after the session. The qualitative interviews suggest the foot massage was well tolerated and although taking staff away from their work resulted in some participants feeling guilty about taking time out, a 10-min foot massage was feasible during a working shift. Conclusions: This pilot trial provides data to support the feasibility of the study in terms of recruitment and consent, the intervention and completion rates. Although the outcome data should be treated with caution, the pilot demonstrated the foot massage intervention showed trends in improved mood, reduced anxiety and lower blood pressure in long-term care staff working with older people with dementia. A larger study is needed to build on these promising, but preliminary, findings.